2009
DOI: 10.1088/0022-3727/42/13/135303
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured anodic iron oxide film as photoanode for water oxidation

Abstract: Two different configurations of photoanodes based on anodic iron oxide were investigated for photoelectrochemical water oxidation. A self-ordered and vertically oriented array of iron oxide nanotubes was obtained by anodization of pure iron substrate in an ethylene glycol based electrolyte containing 0.1M NH4F + 3 vol% water (EGWF solution) at 50 V for 15 min. Annealing of the oxide nanotubes in a hydrogen environment at 500 °C for 1 h resulted in a predominantly hematite phase. The second type of photoanode w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
120
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(127 citation statements)
references
References 63 publications
7
120
0
Order By: Relevance
“…For example, it has been frequently suggested that the alignment of hematite's high mobility planes perpendicular to the substrate was necessary to achieve good electron transport through the material 13,26,[38][39][40] because a correlation between texturing and photocurrent was observed. A calculation of the potential drop across the bulk in hematite electrodes-about 6 µV-rules out this possibility, however (see Supplementary Information).…”
mentioning
confidence: 99%
“…For example, it has been frequently suggested that the alignment of hematite's high mobility planes perpendicular to the substrate was necessary to achieve good electron transport through the material 13,26,[38][39][40] because a correlation between texturing and photocurrent was observed. A calculation of the potential drop across the bulk in hematite electrodes-about 6 µV-rules out this possibility, however (see Supplementary Information).…”
mentioning
confidence: 99%
“…However, recent reports disclosed that nanoporous and nanotubular anodic 15 films were formed on iron in ethylene glycol or glycerol electrolyte containing fluoride and small amounts of H 2 O. [17][18][19][20][21][22] The anodic films thus formed are mainly amorphous and highly contaminated with fluoride species; however, they are readily converted to nanoporous or nanotubular α-Fe 2 O 3 , which is of potential interest as a photoanode for water splitting, 17,20,23 as a photoelectrocatalyst 24 and as electrodes in 20 electrochemical capacitors. 25 In the pores of the anodic oxide on iron, it is expected that PPy is deposited by the electropolymerization of pyrrole, similar to electropolymerization in porous anodic alumina templates.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, fluoride-containing organic electrolytes have been utilized to form self-organized nanotubular and nanoporous anodic films on titanium [3,4], zirconium [5,6], niobium [7], tantalum [8] iron [9][10][11] and stainless steel [12]. The use of organic electrolytes enables the formation of thick porous anodic films on iron and stainless steel, and improves the uniformity of the self-ordered pore or nanotubular array as well as the thickening of the anodic films.…”
Section: Introductionmentioning
confidence: 99%